CUSTOMS PROCEDURES WITH ECONOMIC IMPACT AND FISCAL EFFECTS FROM THE USE OF THESE PROCEDURES IN KOSOVO - Mehmetaj, Yll (International Scientific Journal Vision, 2020)
The paper addresses some of the important issues related to customs procedures with economic impact in the Republic of Kosovo, their functioning, impact on budget revenues in Kosovo, and their fiscal role in economic growth and development of the country. Customs procedures with economic impact are procedures that are developed and applied in order to achieve economic prosperity, and since small and open economies have to devote most of their activity to import, and particularly to the export component, then the use of these procedures will serve greatly to faster economic development and will have a direct impactboth in the growth of imports and exports as well as in the possible improvement of overall economic performance